BIOGRAPHICAL METHOD IN PSYCHOLOGY AND SOCIOLOGY - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The consequences and collisions of the wide dissemination and methodological differentiation of the biographical method in the modern humanitarian scholarship are considered in the article.